Сирийские беженцы в Турции: картография, политика и перспективы интеграции (Вестник КазНУ. Серия Востоковедения, 2017)
In March 2017 the civil war in Syria will enter its 6th year leaving behinda country torn apart by a fight between regime and opposition forces.The conflict in Syria has forced 11 million Syrians to migrate safer locationsboth inside the country and abroad. As a result, 4.86 million Syrians hadfled to neighboring countries where Turkey has accepted almost half ofthe total number of refugees abroad and since the start of the civil war hasspent $12.1 billion in order to cover their basic humanitarian needs. Currently,Syrians are given temporary protection status which allows to themto access to basic needs such as health, education and legal assistanceservices through a provisional identity card. Starting from January 2016Turkish government allowed them to obtain a work permit and renewedits 1994 Asylum regulation with more up to date modern new Law onForeigners and International Protection in 2013.